Sustainable biofuel: policy view for commercial aviation in Malaysia - Mohd Noh, Hazariah; Yahaya, Nur Halimatun Radziah; Rodrigo, G. A.; Abdul Rahman, Nur Afdzillah; Yusof, M. R.; Othman, J.; Romli, Fairuz Izzuddin (Science Publishing Corporation, 2018)
The depletion of fossil fuel and the fuel price have urged the world to discover alternative ways of replacing existing fuel with renewable energy for sustainability, hence benefitting the environment. A series of test and scheduled flights have been carried out over the years. This paper views the biofuel policy available in Malaysia, as well as in other developing countries with regards to commercial aviation. To understand and emphasize the importance of having a biofuel policy, the aviation industries need to work in line with the government by reviewing the related policies of biofuel and the authority's concern related to the environment. In future, Malaysia will need to abide by the European Emissions Trading Scheme (EU ETS), thus creating the urgency in utilising the alternative energy. By viewing the various incentives available from the United States and EU, that can be a benchmark towards the recommendable policy that might be carried out in Malaysia.